DIVERSIFIKASI PRODUK TERHADAP PENJUALAN LAMPU ROMANTIS BATU AKIK (LAPIS BATIK) PURBALINGGA - Muhammad Faizin; Nur Azizah; Fitri Hayati (Program Studi Magister Manajemen Universitas Advent Indonesia, 2019)
The increasing number of agate requests in the national market has resulted in an increase in the number of agate orders for each region. Including in Purbalingga Regency as one of the agate producing areas. Increased interest in the community made craftsmen and marketers soar. But there was a decline of 80% compared to when it became a trending topic. This causes the selling value of agate to decrease. Based on these data, this study aims to increase the selling value of agate by diversifying products that are unique, creative, and innovative. The product is named LAPIS BATIK (Lampu Romantis BatuAkik). This study uses an analysis of growth rates and data analysis on the sale of newproducts while the method is a descriptive research method with a case study approach.The results of this study are to prove that product diversification has contributed well intotal sales volume and turnover of total sales after product diversification and thepercentage of products sold is 88.89% of total production for four months of sales with atotal income of Rp. 6,100,000.00 .